2020
DOI: 10.1101/2020.04.07.20056788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE-inhibitors and Angiotensin-2 Receptor Blockers are not associated with severe SARS-COVID19 infection in a multi-site UK acute Hospital Trust

Abstract: Background: The SARS-Cov2 virus binds to the ACE2 receptor for cell entry. It has been suggested that ACE-inhibitors, which are commonly used in patients with hypertension or diabetes and which raise ACE2 levels, may increase the risk of severe COVID-19 infection. Methods: We evaluated this hypothesis in an early cohort of 205 acute inpatients with COVID-19 at King'

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 25 publications
11
118
0
5
Order By: Relevance
“…et al found a slightly lower rate of severe outcomes which included admission to the intensive care unit, the use of noninvasive or invasive mechanical ventilation, or death in patients on ACEI/ARB (24.8%) versus no ACEI/ARB (24.9%). [12,13,15,16,19,20,[23][24][25][26][27]. (Table 2) On the contrary, Guo [13,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…et al found a slightly lower rate of severe outcomes which included admission to the intensive care unit, the use of noninvasive or invasive mechanical ventilation, or death in patients on ACEI/ARB (24.8%) versus no ACEI/ARB (24.9%). [12,13,15,16,19,20,[23][24][25][26][27]. (Table 2) On the contrary, Guo [13,23].…”
Section: Resultsmentioning
confidence: 99%
“…Further, abstracts of 98 articles were read and subsequently, the full text of 41 articles were reviewed. Of these, sixteen articles were shortlisted which compared the clinical and/or mortality outcomes of COVID-19 patients on ACEI or ARB with non-users [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Finally, these sixteen studies were included for review and out of these, nine and five studies were included in the meta-analysis of mortality and severity outcomes in COVID-19 patients on ACEI/ARB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Side effects of RAAS manipulation are understandably a cause for concern, specifically hypotension and acute kidney injury in the setting of acute illness. The most severe risks of ARBs [111,112] Finally, in addition to the inhibitory effects on AT1R, a pre-print publication from Iran [113] identified losartan as a potential candidate treatment based on molecular docking and dynamic simulation. In addition to the effects on angiotensin homeostasis, therefore, losartan may directly inhibit the viral macrodomain and cell cycle.…”
Section: Ace2 Binding Viral Infection Sars-covmentioning
confidence: 99%
“…The study cohort was defined as all adult inpatients testing positive for SARS-Cov2 by reverse transcription polymerase chain reaction (RT-PCR) between 1 st March to 5 st April 2020 at a multi-site acute NHS hospital in South East London (UK Starting from our previous model 26 , further supervised training improved detection of annotations and meta-annotations such as experiencer (is the concept annotated experienced by the patient or other), negation (is the concept annotated negated or not) and temporality (is the concept annotated in the past or present) with MedCATTrainer. Meta-annotations for hypothetical, historical and experiencer were merged into "Irrelevant" allowing us to exclude any mentions of a concept that do not directly relate to the patient currently.…”
Section: Patientsmentioning
confidence: 99%